The beneficial plant growth-promoting association of Rhizobium leguminosarum bv. trifolii with rice roots - Yanni, Youssef G.; Rizk, Rizk Y.; El-Fattah, Faiza K. Abd; Squartini, Andrea; Corich, Viviana; Giacomini, Alessio; de Bruijn, Frans; Rademaker, Jan; Maya-Flores, Jaime; Ostrom, Peggy; Vega-Hernandez, Maria; Hollingsworth, Rawle I.; et al. (Commonwealth Scientific and Industrial Research Organisation, 2001)
This paper originates from an address at the 8th International Symposium on Nitrogen Fixation with Non-Legumes, Sydney, NSW, December 2000 This paper summarizes a multinational collaborative project to search for natural, intimate associations between rhizobia and rice (Oryza sativa L.), assess their impact on plant growth, and exploit those combinations that can enhance grain yield with less dependence on inputs of nitrogen (N) fertilizer. Diverse, indigenous populations of Rhizobium leguminosarum bv. trifolii (the clover root-nodule endosymbiont) intimately colonize rice roots in the Egyptian Nile delta where this cereal has been rotated successfully with berseem clover (Trifolium alexandrinum L.) since antiquity. Laboratory and greenhouse studies have shown with certain rhizobial strain–rice variety combinations that the association promotes root and shoot growth thereby significantly improving seedling vigour that carries over to significant increases in grain yield at maturity. Three field inoculation trials in the Nile delta indicated that a few strain–variety combinations significantly increased rice grain yield, agronomic fertilizer N-use efficiency and harvest index. The benefits of this association leading to greater production of vegetative and reproductive biomass more likely involve rhizobial modulation of the plant’s root architecture for more efficient acquisition of certain soil nutrients [e.g. N, phosphorus (P), potassium (K), magnesium (Mg), calcium (Ca), zinc (Zn), sodium (Na) and molybdenum (Mo)] rather than biological N2 fixation. Inoculation increased total protein quantity per hectare in field-grown grain, thereby increasing its nutritional value without altering the ratios of nutritionally important proteins. Studies using a selected rhizobial strain (E11) indicated that it produced auxin (indoleacetic acid) and gibberellin [tentatively identified as gibberellin (GA 7 )] phytohormones representing two major classes of plant growth regulators. Axenically collected rice root exudate significantly enhanced E11’s production of this auxin. This strain extensively colonized the rice root surface under gnotobiotic culture conditions, producing distributions of spatial patchiness that would favour their localized erosion of the epidermal surface, colonization of small crevices at epidermal junctions as a possible portal to enter into the root, and quorum sensing of diffusible signal molecules indicating that their nearest bacterial neighbours are in close proximity in situ. Studies of selected rhizobial endophytes of rice indicated that they produced cell-bound cellulase and polygalacturonase enzymes that can hydrolyze glycosidic bonds in plant cell walls, and non-trifolitoxin bacteriocin(s) that can inhibit other strains of clover rhizobia. Strain E11 was able to endophytically colonize rice roots of varieties commonly used by Filipino peasant farmers, and also to stimulate genotype-specific growth-promotion of corn (Zea mays, maize) under field conditions. An amalgam of these results indicate some rhizobia have evolved an additional ecological niche enabling them to form a three-component life cycle including a free-living heterotrophic phase in soil, a N2-fixing endosymbiont phase within legume root nodules, and a beneficial growth-promoting endocolonizer phase within cereal roots in the same crop rotation. Our results further indicate the potential opportunity to exploit this newly described, plantrhizobia association by developing biofertilizer inoculants that may assist low-income farmers in increasing cereal production (especially rice) with less fertilizer N inputs, fully consistent with both sustainable agriculture and environmental safety.